A literature review on role of physical activity in the prevention and treatment of depression - Lompart, Albert; Wabiszewicz, Michał; Kosarewicz, Albert; Woźniak, Łukasz; Krysiak, Patrycja (Quality in Sport, 2025)
Purpose This review explores the role of physical activity in preventing and treating depression across diverse groups. It critically assesses recent evidence and identifies the most effective exercise interventions by systematically analysing studies published between 2017 and 2025. Methods The analysis covered peer-reviewed randomised controlled trials, systematic reviews, and meta-analyses focusing on links between various physical activities and depression symptoms in different age groups. Results The findings confirm that physical activity has clear antidepressant effects, with moderate to large effect sizes depending on exercise type and intensity. Aerobic exercise shows standardised mean differences (SMDs) from -0.496 to -1.156, resistance training shows SMDs between -0.66 and -1.06, and high-intensity interval training provides moderate effects (SMDs of -0.42 to -0.496). Suggested mechanisms include increased brain-derived neurotrophic factor, improved neurotransmitter function, lower inflammation, and balanced HPA-axis activity, which help reduce depressive symptoms. Conclusion Physical activity is a safe, evidence-based, and cost-effective option for preventing and treating depression. Adding structured exercise programmes to everyday routines and healthcare practice can improve mental wellbeing, quality of life, and help lower the global burden of depressive disorders across all age groups.